Plant physiology - Taiz, Lincoln; Taiz, Lincoln; Zeiger, Eduardo (Sunderland, Sinauer Associates, 2010)
The fifth edition sets the standard for textbooks in the field, making plant physiology accessible to virtually every student. Taiz and Zeiger collaborate with a stellar group of contributing plant biologists to produce a current and authoritative volume that incorporates all the latest findings and 2 new chapters
Includes bibliographical references.; Appendices A1-A3p.; Glossary G1-G23p.; Index I1-I40p.
Keywords: Plant physiology; Botany